Wild Edible Vegetables of Lesser Himalayas Ethnobotanical and Nutraceutical Aspects, Volume 1 - Abbasi, Arshad Mehmood; Shah, Munir Hussain; Khan, Mir Ajab (Springer International Publishing : Imprint: Springer, 2015)
Our intention with this book was to present the reader with the most accurate, significant, and up-to-date background and knowledge in the areas of ethnomedicinal and nutraceutical vegetation for the Lesser Himalayas in a comprehensive text. Wild Edible Vegetables of Lesser Himalayas provides a complete review of over 50 important plants of this region and details each species including photographs, botanical name, local name, family, flowering and fruiting period, status and habitat, parts used, distribution, ethnobotanical uses, cultural aspects, medicinal uses, and nutraceutical aspects. Medicinal uses include mode of preparation, method of application and diseases studied; cultural aspects and index; nutraceutical data provides analysis of fats, proteins, fibers, carbohydrates, ash, moisture content, dry matter, and energy value; elemental analysis includes various essential and toxic metals; phytochemical screening includes total phenolics, flavonoids, flavonols and ascorbic acid, and antioxidant potential in terms of DPPH scavenging activity, hydroxyl radical scavenging activity, H2O2 scavenging activity, Fe2+ chelating activity, ferric reducing antioxidant power, and phosphomolybdenum assay for each species. Wild Edible Vegetables of Lesser Himalayas is a concise and handy guide for scientists, scholars, and students interested in the study of agriculture, food science, nutraceutical science, bioscience, biodiversity, applied ethnobotany, ethnoecology, and ecology. .